It All Began with an Error : The Nomofungin/Communesin Story - Siengalewicz, Peter; Gaich, Tanja; Mulzer, Johann (My University, 2008)
The communesin/nomofungin/perophoramidine story is an impressive example of how biogenetic considerations can lead to the correction of structural misassignments and inspire synthetic chemists with new, fruitful ideas. Intensive studies by a number of research groups culminated in the total synthesis of perophoramidine by the Funk research group in 2004. In 2007, Qin and co-workers completed the first total synthesis of a communesin.
Keywords: 540